Realization of international legal norms in the sphere of childs rights protection in the Republic of Kazakhstan - Akimzhanova, M.T.; Ilyassova, G.A. (KSU Publ., 2017)
The rights and freedoms of the person and the citizen, their recognition, respect and protection is a basis on which the democratic government of the modern states is based. Origin and protection of institute of human rights it was originally carried out within the national legislation though value of some acts overcame borders of the national states and promoted development of national consciousness in other countries. For protection of the rights and freedoms of the minor, the current legislation, provided a specific set of means and methods of protection: international legal mechanism of protection of human rights; judicial protection; administrative actions of executive authorities; lawful self-defense by the person of the rights. Analyzed questions of international legal standards implementation in the sphere of respect for the child`s rights in the Republic of Kazakhstan in this article. Carried out the review of international legal documents and generally accepted international standards, and also the national legislation on protection of children rights, recommendations about improvement of the legislation in the sphere of children rights protection are offered.
Қазақстан Республикасында бала құқықтарын қорғау саласындағы халықаралық-құқықтық нормалардың іске асырылуы
Реализация международно-правовых норм в области защиты прав ребенка в Республике Казахстан
Keywords: The rights of children; the child; protection of children rights; the international standards on children rights protection; implementation of international legal standards